Arabidopsis Thaliana: From Weed to Model Organism. Issue 19 (2nd December 2019) - Diaz, Michael
Abstract: Arabidopsis thaliana is a small plant of significant economic and agronomic importance. While Arabidopsis is not a crop plant, it is not so different in its fundamental properties. Arabidopsis is a member of the Brassicaceae family, which constitutes one of the world's most economically important plant groups. According to the United Nations, globally Brassicaceae crops are worth 31 billion, and the number is likely to increase since a number of related species within this family are underutilized edible varieties. Its small size is an advantage to researchers with limited space and funding; simply put, a smaller plant requires fewer resources. Arabidopsis has been studied most intensely for the last 40 years and officially became a model plant in the late 1990s. Since then, the community has developed genetic and genomic resources so numerous that the barrier to entry to studying Arabidopsis is relatively low. This article provides a primer to how Arabidopsis came to be a model organism and highlights essential techniques every Arabidopsis researcher should be aware of to advance the pace of discovery. © 2019 by John Wiley & Sons, Inc.